Transfer of nitrates from the Tafna watershed (North-West Algeria) to the Mediterranean sea - approach coupling measurements, modeling and changing scale to the biggest coastal rivers in North Africa - (:unkn) unknown (My University, 2018)
In semi-arid and highly anthropized area characterization and quantification of pollutant transfers in surface waters and to the sea is important to understand and to help better management of water resources, especially in North Africa, where the of obtaining data in quantity and sufficient quality is difficult. This study investigates mechanisms transfer of nitrate and sediment in the Tafna watershed (7200 km2) and at the biggest coastal rivers in North Africa with an approach, coupling in situ measurements and SWAT model (Soil and Water Assessment Tool). The in situ part made it possible to quantify the quantity of nitrates exported by the different Tafna sub-basins. It also highlighted the contribution of the watershed to eutrophication of the Mediterranean Sea by measuring the quantities of nitrates transported to marine waters. The quantities transferred are important in the high water season while they decrease in the rivers during the dry season. The results highlighted the factors that influence the nitrates flux and nitrate concentrations; the land use has a great influence on the nitrate flux in the Tafna. The study stations were classified according to the eutrophication gradient. The upstream stations with high nitrates concentration, oppose downstream stations. Modeling results showed that Tafna's surface water comes from surface runoff (59%) and lateral flow (40%), while the contribution from groundwater was insignificant (1%). Tafna has transferred an average annual amount of 2942 t.yr-1 of sediment to the sea. SWAT has also shown that dams store a large amount of sediment, over 27 000 t.yr-1 (90% of the sediments transported by Tafna). The model also reproduced the nitrates flux at the gauging stations between 2003 and 2011. The Tafna carries 37-86 tN.yr-1 to the Mediterranean Sea and Tafna dams store a large quantity of nitrates [80 and 486 tN.yr-1], which represents an average 62% of the total amount of nitrates transported annually
Keywords: African Research